A Game-Based Repeated Assessment for Cognitive Monitoring: Initial Usability and Adherence Study in a Summer Camp Setting. - Flynn, Rachel M.; Colón-Acosta, Nirmaliz; Zhou, Jimmy; Bower, Jeffrey (Journal of Autism & Developmental Disorders, 2019)
The current feasibility study examined the adherence, reliability, and assessment potential of an evidence-based game-like mobile Monitoring Tool (Akili Interactive Labs), to monitor 100 participants' cognition for eight sessions at a summer camp for children with special needs. A validated measure of attention was administered at baseline. In the last session, participants completed an exit questionnaire. The Monitoring Tool was found to be enjoyable, and showed a high rate of adherence. No Monitor-related adverse events were reported. Monitor metrics showed good reliability across repeated measurements, indicating it is stable over long-term cognitive monitoring. There was evidence that the Monitoring Tool was able to detect differences in cognition between the children diagnosed with attention deficit hyperactivity disorder and autism spectrum disorders.